Impact of Nutrition Labeling on Food Choices and Diet Quality in France - Garcia, Jules (Global Journal of Health Sciences, 2024)
Purpose: The aim of the study was to analyze the impact of nutrition labeling on food choices and diet quality in France. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: In France, the Nutri-Score labeling system has been found to significantly influence food choices towards healthier options by providing clear nutritional information on packaged foods. Studies indicate that consumers are more likely to select products with higher Nutri-Score ratings, indicative of healthier nutritional profiles, leading to improved overall diet quality and potentially reducing the risk of diet-related health issues. Unique Contribution to Theory, Practice and Policy: Health belief model (HBM), theory of planned behavior (TPB) & social cognitive theory (SCT) may be used to anchor future studies on impact of nutrition labeling on food choices and diet quality in France. Emphasize interpretive labels that simplify complex nutritional information and facilitate quick comprehension across diverse demographic and cultural groups. Advocate for harmonized nutrition labeling regulations at national and international levels to ensure consistency and comparability across products and regions.